Computational fluid dynamics and subchannel analysis of lead–bismuth eutectic-cooled fuel assembly under various blockage conditions. (5th January 2020) - Liu, X.J.; Yang, D.M.; Yang, Y.; Chai, X.; Xiong, J.B.; Zhang, T.F.; Cheng, X.
Highlights: STAR-CCM+ and COBRA-YT are feasible for LBE bundle thermal-hydraulics simulation. With increases in blockage area and thickness, temperatures increased but mass flow decreased. Cladding temperature under the most severe blockage accident was still below the melting point. Abstract: In recent years, extensive research has been carried out for liquid metal-cooled reactors. One of the design challenges is keeping the cladding temperature below the design limit, especially under local blockage. Thus, accurate prediction of coolant and fuel cladding temperatures is necessary for thermal-hydraulics analysis of LBE-cooled fuel assemblies. In this study, CFD and subchannel analysis were carried out to investigate the effect of various blockage accidents on the thermal-hydraulic performance of a single fuel assembly. Based on actual geometry and material properties, modelling of a single fuel assembly was established, and five blockage accidents were numerically simulated by the CFD software STAR-CCM+. Temperature variations along the axial direction of the cladding inner surface and the subchannel centre were obtained and compared. The influence of blockage parameters on the coolant reverse flow was investigated and detailed information on flow fields was obtained. The maximum temperature increase occurred inside the blockage, which influenced flow and heat transfer behaviour. Finally, a comparison of key parameters between STAR-CCM+ and COBRA-YT was conducted to show the applicability of the two codes. The results indicated that the cladding temperature during a blockage accident should be evaluated to avoid exceeding the design criteria.